Perfil do comportamento do consumidor maduro em viagens de lazer - Acevedo, Claudia Rosa (1998)
This study focuses on understanding the consumer behavior of seniors (the over 55 traveIers) and nonseniors (young adults between 25 and 54 years oId). The main purposes of the study are: to describe the behavior of the eIderly traveIers in pIeasure trips and investigate the reIationship between age and other traveI reIated characteristics, in order to examine if the senior pIeasure traveI market is different from younger segments. A number of similarities and differences emerged from the study which invoIved a snow balI sampIe of 122 oIder peopIe and 151 young adults. SpecificalIy, the results indicate four distinct traveI reIated characteristics: reasons for traveI, IifestyIes profiles, months the trip took pIace and the activities taken during the trip.